Identification of Rock Characteristics Using the Microtremor Inversion Method at Air Putih Geothermal Field, Lebong Regency - M Taufiqurrahman Syah; Nanang Sugianto (Talenta Publisher, 2024)
Research has been carried out to identify rock characteristics based on Vs values using the microtremor method in the Air Putih geothermal field, Lebong Regency, which aims to determine the geothermal prospect area on rock characteristics using Vs values based on the microtremor method. The data obtained in this study were 20 measurement points obtained from data analysis by obtaining the H/V curve through Geopsy software and HVSR inversion to obtain the Vs value of the inverse. The results of this calculation indicate that at a depth of 0-4 meters the homogeneous Vs value 200 m/s, at a depth of 4 meters the Vs value 200-440 m/s, at a depth of 20 meters the value of Vs 440 -880 m/s and a depth of 20 meters homogeneous Vs value of 880 m/s and for the distribution of Vp values, at a depth of 0-5 meters the Vp values vary between 2000-2900 m/s, at depths of 6-20 meters in general the value of the Vp wave velocity is the same in the range of 3100-3800 m/s and at depth 21-100 meters the Vp value ranges from 3900-5100 m/s. This shows that the greater the depth, the denser the rock.